The Method of Building a Wide Span Structure at Gelora Bung Karno Aquatic Stadium - Yolanda Azhar Susanti; Dewi Rachmaniatus; Tika Novis Putri (Rumoh Journal of Architecture, 2024)
According to the results and obervation, in the first construction in 1960, the Aquatic Stadium Gelora Bung Karno (GBK) with an area 24,000 m². GBK Aquatic Stadium is an international outdoor building that was inaugurated directly by the first president of Indonesia at that time Soekarno and Hatta, which had 4 swimming pools, namely competition pool, diving pool, water polo pool and training pool. GBK Aquatic Stadium was first designed by well-known architect Federick Silaban, which was later renovated in 2017 by architect Andra Matin, this renovation is because there must be conformity of the international stadium by following international swimming standards, namely the Federation Internationale de Natation (FINA) which one of the standards is indoor, the potential of the indoor stadium is related to the impact of the weather in Indonesia which is uncertain. In addition, the reason for renovating the GBK Aquatic Stadium is because there is a major event, namely is Asian Games which was held in Indonesia in 2018. The result of the renovation of Andra Matin is only on the roof. In accordance with the government's appeal at was, GBK Aquatic Stadium was a historic building, where the government did not allow any changes to the initial design of the stadium, Andra Matin also made new columns outside GBK Aquatic Stadium building as a support for the new roof. Andra Matin designed the roof of GBK Aquatic Stadium with a space frame wide span structure system, by applying form of fluidity or form of water properties. There are 5 waves on the right side, and flat on the roof on the left. According to Andra Matin, the water was exposed to the waves then calmed down. Since the renovation and Asian Games 2018, this area has attracted the attention of many people because of its unique building.